Ovine abortion and stillbirth investigations in Australia. Issue 3 (1st December 2020) - Clune, T; Beetson, S; Besier, S; Knowles, G; Paskin, R; Rawlin, G; Suter, R; Jacobson, C
Abstract : Fetal loss and lamb mortality between mid‐pregnancy and weaning are important economic and welfare issues for the Australian sheep industry. The aim of this study was to determine common causes of ovine abortion and stillbirths based on submissions to veterinary laboratories and identify factors that impact the determination of an aetiological diagnosis. Data for 529 investigations on abortion or stillbirth between 2000 and 2018 were retrieved from four state veterinary laboratories in Western Australia, South Australia, Victoria and Tasmania. An aetiological diagnosis was made for 57% of investigations. Investigations that included placental tissue samples were more than twice as likely to have an aetiological diagnosis compared to investigations without placenta (P = 0.017, 95% confidence interval 1.1, 4.5). Of the investigations where an aetiological diagnosis was made, 81% involved infectious abortion, with Campylobacter spp. (32%), Listeria spp. (25%) and Toxoplasma gondii (9%) being the three most common abortigenic pathogens implicated. The remaining 19% of investigations with an aetiological diagnosis included a wide range of infectious and non‐infectious diseases. Diagnoses made varied year to year and between states. No evidence of exotic abortigenic pathogens were reported. Veterinary practitioners can improve the probability of an aetiological diagnosis by emphasising to farmers the importance of collecting any aborted material, especially placenta, and appropriate storage of the tissues until they can be submitted to the laboratory. Some diseases that cause abortion in Australian sheep have zoonotic potential, and veterinary practitioners play an important role in educating clients about appropriate hygiene when handling pregnant and lambing ewes or any aborted material.